Employment and Labour Productivity vs Economic Development of Polish Regions (2000–2013) - Jarmołowicz, Wacław; Kuźmar, Sławomir (Olsztyn Economic Journal, 2017)
The main goal of the present article is to identify the main determinants and mechanisms through which the level and growth rate of labour productivity as well as selected aspects of employment influence the economic development of Polish regions over the 2000–2013 period. The conducted analysis suggests that among such productivity and employment-related factors as hourly labour productivity, total hourly work time per person employed, effectiveness of labour market, level of participation rate and demographic structure, of greatest importance for the economic development of Polish regions is their inner effectiveness reflected by the level of hourly labour productivity.